The man-biting activity of phlebotomine sand flies (Diptera: Psychodidae) in a tropical wet forest environment in Colombia - Porter, Charles H.; Foliart, Gene R. (Arquivos de Zoologia, 1981)
The purpose of this study was to investigate the temporal and spatial attributes of the man-biting activity of phlebotomine sand flies in a Tropical Wet Forest environment. The study was undertaken in a sparsely populated region of the east central portion of the Department of Antioquia, Colombia. With three two-man teams as bait, catches of approximately 10 hours duration during the day and approximately 13 hours for the night and twilight period were made at three separate forest locations and six diverse clearing sites. In the forest series of catches, the predominant man-biting species and their percentage of the catch were Lutzomyia hartmanni (56%), L. trapidoi (22%), and L. yuilli (13%). In the clearing series of catches the predominant species were L. hartmanni (56%), L. gomezi (16%), L. yuilli (9%), and Warileya rotundipennis (9%). For most species, both the magnitude and vertical stratification of their man-biting activity tended to be quite variable between the three forest sites. These differences were thought to be related to local variations in forest structure. Between-site differences in the magnitudes of biting activity were ¡east pronounced in the understory. L. trapidoi, and to a lesser extent L. yuilli, were reluctant to bite at ground level in either the forest or clearing habitats. Their diminished biting activity at ground level appeared to primarily account for the greater similarity of the clearing catches to the forest floor catches than to those in the understory and canopy. In the clearing series of catches, the biting activity of L.hartmanni, L. trapidoi, and L. yuilli was detected to be significantly greater at the two forest edge sites than at those sites within the clearing. Diversity of man-biting activity in the clearing habitat was determined to be greatest at a site situated at the edge of pioneer vegetation and pasture. The pioneer vegetation extended to this location from the forest about 130 m away. The man-biting activity of phlebotomine sand flies in the Providencia study area was primarily nocturnal although crepuscular patterns were exhibited by L. bifoliata within the forest and by L. gomezi at the clearing sites. The temporal pattern of biting activity of each of the predominant forest species, i.e., L. hartmanni, L. trapidoi, and L. yuilli, was quite variable from one night to another and there was often a sharp peak in the biting activity. When such variations were averaged, the summarizing pattern tended to distort the true nature of the biting activity and only defined a rather broad interval of time in which biting activity was likely to be concentrated. There was no indication of a nightly pattern of vertical movement by any of these three species. The biting activity of most species appeared to be concentrated at a somewhat earlier time in the clearing habitat than in the forest. The magnitude of man-biting activity for all species combined was relatively uniform throghout the year; however, the dry season was unusually wet. Most of the individual species also did not appear to have pronounced seasonal fluctuations in biting acitivity although L. panamensis was a notable exception. The patterns of man-biting activity exhibited by L. gomezi suggest that it is the species most likely to transmit dermal leishmaniasis to man in the region where our study was conducted. The phlebotomine sand fly assemblage of the Providencia study area is compared with that described from other locations in Colombia and Panamá. For each of the common man-biting species in the study area, a review of the literature pertaining to their biology is included.